The effectiveness of violin textbooks at the primary level in the music study program - Dewi, Vivi Ervina; Sarjoko, Moh; Sunarto, Sunarto (Imaji: Jurnal Seni dan Pendidikan Seni, 2023)
The research conducted aims to determine the effectiveness of the main level violin textbook that has been made in terms of students' violin playing skills during pretest and posttest at the Music Study Program, Universitas Negeri Surabaya. The use of quantitative methods with the type of quasi experiment and one-group pretest-posttest design in this study. The use of inferential analysis in the form of a normality test with the Shapiro-wilk method with a sig value 0.05 of 0.889 and 0.906 so that the data is normally distributed (symmetrical). Hypothesis testing using the paired sample t test found that the average test of violin playing skills during the pretest was 76.09 and the posttest was 78.82, an increase of 2.73. Other results are also shown by t count (t0) which is -2.725 and t table which is 2.228, because t count is negative then two tailed hypothesis testing is done with left side testing with the results that H0 is rejected and H1 is accepted. The mean difference figure of -2.727 shows the average difference in violin playing skills tests on pretest and posttest activities. The significance results of the pretest and posttest activities show that the correlation between the two conditions is unidirectional, strong, and significant. These results are shown in the significance value which is smaller than 0.05 (0.000 0.05). Therefore, the main level violin textbook made is said to be effective in terms of the three results obtained.Keywords: textbook, violin, skills